Analisis Strategi Komunikasi Pemasaran @Ninetysixvintages Pada Media Sosial Instagram - Raffi, Muhammad; Dianita, Indria Angga (Jurnal Pustaka Komunikasi, 2024)
This study aims to determine the marketing communication strategy of @Ninetysixvintage through Instagram social media to support sales. This research uses a qualitative approach. A qualitative approach is a research method that focuses on an in-depth understanding of human phenomena, including in this case, marketing communication strategies on Instagram social media. This method involves data collection that is descriptive and narrative, with the aim of exploring a deeper understanding of the research subject. The results of this study are the message strategy and media strategy used by @Ninetysixvintages in their marketing communication on the Instagram social media platform. The applied communication strategy involves various aspects, including information content and creative. In terms of information content, @Ninetysixvintages focuses on delivering information about the product and its characteristics. While in terms of creative messaging on the Instagram platform, @Ninetysixvintages divides it into rational and emotional elements seen in their posts. In addition, there are also media usage strategies implemented by @Ninetysixvintages, including media selection and target market identification. In an effective marketing communication effort on the Instagram social media platform, @Ninetysixvintages utilizes various features such as followers and following, captions, interaction in the form of likes and comments, tagging, the use of hashtags, Instastory, live broadcasts, and direct messages to support the marketing communication strategy they implement.